Developing a scale to assess Islamic values application in quality management: a study among Malaysian organisations / Amal Hayati Ishak - Hayati Ishak, Amal (2016)
Quality management has long been established at the advent of Industrial Revolution. Since then, the widespread of quality management across the globe has been owed to the Western and Japanese quality gurus. Despite overwhelming influence of both cultures, contemporary scholars have consistently discussed Islamic perspectives of quality management since the 1990s. Their discussion is enlightened with primary sources of Islam, reflecting a plethora of Islamic values embedded in quality management practice. In parallel, a Malaysian national-level standard, the MS 1900 or the Shariah-based Quality Management System has been established, aiming towards internalization of Islamic values. The standard initiates the 'Organisational Values' clause which requires organisations to apply, monitor and measure values application. Although MS 1900 emphasizes on Islamic values measurement, existing scales used by organisations are self-developed and unstandardized. Yet, their validity information is ambiguous. Though the MRPI (Muslim Religiosity Personality Inventory) and IWE (Islamic Work Ethics) scale measure Islamic values, they apply for individual-level measurement and not focused on quality management. Moreover, literature-based scales are built on Western theoretical framework without due reference to Islamic substance. They are also being validated in the Western ambience. Such scales do not match the MS 1900 aspirations. Thus, the main aim in this study is to develop and validate a measurement scale to assess Islamic values application in quality management, named the Islamic Quality Management Scale (IQMS). Following a systematic scale development process, the study proposed eight Islamic value dimensions grounded on relevant Quranic verses and Prophetic traditions. The argument on IQMS content validity was resolved via nonstatistical expert review, followed by statistical Fuzzy Delphi analysis. Later, the reliability of IQMS was confirmed via Rasch Measurement Model. The results showed consistent reliability for both pilot test and actual test, indicated by Rasch analysis of item polarity, item fitness, unidimensionality, scale calibration, item dependency, item reliability and separation as well as person reliability and separation. Based on the analyses, eleven problematic items were removed. The removal was found substantially efficient as it improves the scale's reliability. Thus, the main contribution of this study is the validated IQMS; consists of eight dimensions and 49 items. Additionally, resulted from Rasch analysis on item difficulty and person ability, the study also proposed a set of basic value practices which could inspire organisations planning for MS 1900 certification. The study also proposed another set of advanced practices which could improve value application among MS 1900 certified organisations. The basic and advanced practices were the value added in this study since the MS 1900 is silent on that matter. The IQMS is significant as it contributes to three relevant parties; the policy makers for value application index, the certification body for external auditing purposes and organisations for internal auditing purposes. However, the study was confined to scale development and did not involve any hypotheses testing.